Effect of non-enzymatic browning on flavour, colour and antioxidative activity of dark specialty malts – A review - Coghe, Stefan; Derdelinckx, Guy; Delvaux, Freddy R. (BrewingScience, 2004)
Non-enzymatic browning reactions such as Maillard reactions, caramelisation and pyrolysis, have a considerable impact on the properties of dark specialty malts. The mechanisms and chemical reactions leading to non-enzymatic browning are briefly described. While pyrolysis and caramelisation are restricted to roasting processes, Maillard reactions can occur during the production of all types of malt due to milder reaction conditions. As the Maillard reaction is the most important mechanism of non-enzymatic browning in malt, factors affecting the rate of this reaction including temperature, time, water activity, concentration and type of reactants, pH and occurrence of sulphur compounds are considered in detail. This review specifically focuses on flavour, colour and antioxidative activity. These major dark malt characteristics result from browning products, which pass into dark beer thereby influencing beer colour, flavour and flavour stability. Current knowledge on key compounds responsible for flavour (Strecker aldehydes and heterocyclic compounds), colour (LMW chromophores, melanoidins) and antioxidative activity (reductones and melanoidins) and elements in the chemical structure, which may contribute to these properties, are reviewed. Furthermore, testing procedures for colour determination, instrumental or sensory evaluation of flavour and assessment of antioxidative activity as well as the relationships between the different characteristics are described.